2019
DOI: 10.1177/0020715219849463
|View full text |Cite
|
Sign up to set email alerts
|

Part-time employment as a way to increase women’s employment: (Where) does it work?

Abstract: Part-time employment has repeatedly been proposed as a solution for integrating women into the labor market; however, empirical evidence supporting a causal link is mixed. In this text, we investigate the extent to which increasing part-time employment is a valid means of augmenting women’s labor market participation. We pay particular attention to the institutional context and the related characteristics of part-time employment in European countries to test the conditions under which this solution is a viable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…A weakening of the association between family responsibilities and women's LFP is also consistent with other mechanisms identified in the cross‐national literature of women's LFP, including: the expansion of publicly funded child care, the reduction of lengthy parental leaves, the increasing availability of well‐paid leaves of modest duration (Misra, Budig, and Boeckmann 2011; Pettit and Hook 2009), the availability of part‐time work—at least in Continental and Mediterranean countries (Barbieri et al. 2019), the growth of the public and service sectors (Fodor and Glass 2018), changing social norms (Euwals, Knoef, and Vuuren 2011), and the intergenerational transmission of maternal employment (Fernández, Fogli, and Olivetti 2004). Labor market conditions including those associated with globalization and economic uncertainty are also relevant (Blossfeld and Hofmeister 2006) as is the growth of long work hours in some countries (Cha 2010).…”
Section: Demographic Foundationssupporting
confidence: 83%
“…A weakening of the association between family responsibilities and women's LFP is also consistent with other mechanisms identified in the cross‐national literature of women's LFP, including: the expansion of publicly funded child care, the reduction of lengthy parental leaves, the increasing availability of well‐paid leaves of modest duration (Misra, Budig, and Boeckmann 2011; Pettit and Hook 2009), the availability of part‐time work—at least in Continental and Mediterranean countries (Barbieri et al. 2019), the growth of the public and service sectors (Fodor and Glass 2018), changing social norms (Euwals, Knoef, and Vuuren 2011), and the intergenerational transmission of maternal employment (Fernández, Fogli, and Olivetti 2004). Labor market conditions including those associated with globalization and economic uncertainty are also relevant (Blossfeld and Hofmeister 2006) as is the growth of long work hours in some countries (Cha 2010).…”
Section: Demographic Foundationssupporting
confidence: 83%
“…with lower average working hours) can enable men to assume greater responsibilities within the household, whereas a lower amount of time spent by women on the main job (i.e. through part-time jobs) can allow women with care requirements to reconcile family and work better if they wish to do so (Anxo et al, 2006;Baizan et al, 2016;Barbieri et al, 2019;Keck and Saraceno, 2013;Saraceno and Keck, 2011).…”
Section: Structural and Institutional Conditionsmentioning
confidence: 99%
“…The research shows that when talking about the determinants of part-time employment, we should consider the factors from both supply and demand-side (Barbieri et al, 2019;Euwals & Hogerbrugge, 2004;O'Dorchai et al, 2007). What concerns the supply side, according to O'Dorchai et al (2007), some categories of persons would always prefer to work part-time rather than full-time (and vice versa).…”
Section: Factors Affecting the Rate Of Part-time Employmentmentioning
confidence: 99%
“…This might particularly be the case with regard to young workers (students), young parents, older workers, disabled people and others. According to Barbieri et al (2019), part-time jobs provide opportunities for individuals who would not otherwise be able to participate in the labour market. E.g., many studies have shown that the growing female labour force participation over the last few decades was one of the principal determinants that increased the incidence of parttime employment in many European countries (Euwals & Hogerbrugge, 2004;Barbieri et al, 2019;Booth & van Ours, 2012).…”
Section: Factors Affecting the Rate Of Part-time Employmentmentioning
confidence: 99%